Molecular variability among Brazilian strains of the sugarcane smut pathogen and the genetic basis of host specialization in smut fungi - Benevenuto, Juliana (2017)
Plant pathogens have the ability to quickly overcome host resistance and shift to novel hosts. The (re)emergence of plant pathogens is a major concern in agriculture and in conservation of natural landscapes. The rapid adaptation to hosts and new environments depends on the genetic variability in pathogen populations. Despite of the importance of sugarcane for Brazilian agribusiness and the persistence of the smut pathogen Sporisorium scitamineum in most cropping areas, genetic variation studies are still missing for Brazilian isolates. In the chapters 1 and 2, molecular variability studies were performed for Brazilian and Argentine isolates of S. scitamineum, using molecular markers (AFLP, telRFLP) and sequencing (ITS and a candidate effector gene) strategies. No variation was found in ITS sequences. On the contrary, telRFLP marker generates almost a unique fingerprint for each strain. Two genetically distinct groups were formed by the joint analysis of the AFLP and telRFLP markers. The two groups were the same formed by haplotypes of a candidate effector gene. The presence of polymorphisms that causes non-synonymous mutations in a candidate effector gene potentially involved in the specific interaction with sugarcane may cause distinct performances on host genotypes. S. scitamineum is part of the highly diverse clade of Ustilaginomycetes fungi that includes several smut disease agents. Despite being phylogenetically close and present similar lifestyles, species of smut fungi have distinct and narrow host ranges. Hence, another objective in this thesis was to identify the genetic basis of host specialization in smut fungi using comparative genomics analyses. In chapter 3, the mating-type loci were described in S. scitamineum genome and compared among smut fungi. Transposable elements are the likely mechanism causing chromosomal rearrangements between mating-type loci. The presence of trans-specific polymorphisms at the genes encoding pheromone/receptor proteins suggests a hybridization potential among smut species. In the chapter 4, a broad comparative genomics analysis was performed among nine species of smut fungi infecting distinct hosts. The genetic basis of host specialization in smut fungi is complex and seems to involve a range of evolutionary processes, including gene gain/loss and episodic selection events. Species-specific effectors and positively selected genes will be good candidates for further characterization in regards to their role in host adaptation.